A water-resistance soy protein-based adhesive for various substrates application by incorporating tailor-made hydrophobic nanocrystalline cellulose. (June 2022) - Zeng, Yunchuan; Yang, Weijun; Xu, Pengwu; Ma, Piming
Abstract: In this work, a water resistance soy protein-based adhesive was developed by incorporating tailor-made nanoparticles, which were synthesized through the reaction of nanocrystalline cellulose and octadecylamine and tannic acid. For the soy protein-based adhesive system, the incorporated nanoparticles acted as reinforcer and hydrophobic element to improve the cohesive and water resistance. The obtained adhesive was applied to bond wood, corrugated board, glass, aluminum, and PET. Especially, the dry and wet bonding strength of plywood were 2.9 and 1.1 MPa, registering an increment of 160% and 600%, respectively, when comparing to the pristine soy protein-based adhesive. This work provided an effective strategy to develop water-resistance soy protein adhesive for a broad (er) application range. Graphical abstract: Image 1 Highlights: Cellulose nanocrystalline and Octadecylamine were bonded via the high-reactive tannic acid. A water resistance soy protein-based adhesive was developed by incorporating tailor-made nanoparticles. The nanoparticles acted as reinforcer and hydrophobic elements to improve cohesive and water resistance. The obtained adhesive could be applied to bond wood, corrugated board, glass, aluminum and PET. The dry and wet bonding strength registered an increment of 160% and 600%, respectively.